2022
DOI: 10.1007/s11104-022-05669-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil, climate, and variety impact on quantity and quality of maize root mucilage exudation

Abstract: Aims This study investigated the influence of climate and soil on the exudation rate and polysaccharide composition of aerial nodal root mucilage from drought-resistant and drought-susceptible maize varieties. Methods Two maize varieties were grown in two different soils (sandy-clay loam Acrisol and loam Luvisol) under simulated climatic conditions of their agroecological zones of origin in Kenya and Germany. The exudation rate of mucilage from the aerial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…The DH02 variety exhibited a higher mucilage secretion rate compared to the Kentos variety (Fig. 2a), consistent with findings from previous field and pot experiments (Nazari et al 2020(Nazari et al , 2023. A drought-tolerant barley variety secreted larger quantities of mucilage from its roots than a droughtsusceptible one (Carter et al 2019).…”
Section: Mucilage Secretion Rates Differ Between the Maize Varietiessupporting
confidence: 89%
See 2 more Smart Citations
“…The DH02 variety exhibited a higher mucilage secretion rate compared to the Kentos variety (Fig. 2a), consistent with findings from previous field and pot experiments (Nazari et al 2020(Nazari et al , 2023. A drought-tolerant barley variety secreted larger quantities of mucilage from its roots than a droughtsusceptible one (Carter et al 2019).…”
Section: Mucilage Secretion Rates Differ Between the Maize Varietiessupporting
confidence: 89%
“…We speculate that the breeding of Keops in soils characterized by high microbial activity might have led to its elevated mucilage secretion rate. Similarly, previous research has demonstrated that maize varieties cultivated in a soil with high microbial activity exhibited higher mucilage secretion rates compared to the same varieties grown in a soil with lower microbial activity (Nazari et al 2023).…”
Section: Mucilage Secretion Rates Differ Between the Maize Varietiessupporting
confidence: 55%
See 1 more Smart Citation
“…Several characteristics of root exudates undergo changes during drought. For example, drought-resistant maize ( Zea mays ) varieties exuded 58.2% more mucilage compared to drought-susceptible varieties ( Nazari et al., 2023 ), and the role of mucilage has been linked to enhanced hydrologic conductance at the root-soil interface ( Ahmed et al., 2014 ). The amino acid proline, an osmotic regulator, is known to accumulate in root exudates under drought in citrus ( Citrus sp.)…”
Section: Introductionmentioning
confidence: 99%